Increase in capacity and speed of the direct line Inter 2 in Curitiba-PR: Impacts on atmospheric emissions - Silva, Sara Coimbra da; Amancio, Eduardo Cesar (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – The aim of this study is to estimate the direct impacts of atmospheric emissions with the remodeling of the Inter 2 Line due to speed increase, using a diesel-powered bus fleet in the city of Curitiba, PR.Methodology – A bibliographic survey was conducted, followed by statistical analysis and case application, focusing on studies that evaluated the impact of improvements in bus lanes and operational strategies that led to increased traffic speed on atmospheric emissions.Originality/Relevance – Studies indicate that slow traffic, as well as acceleration, deceleration, and stop-and-go conditions, contribute to an increase in in pollutant gas emissions when compared to roads with fewer intersections, which require fewer stops and facilitate higher speeds. In this regard, the research is noteworthy for examining the relationship between the optimization of bus lanes and increased speed, while estimating the reduction of pollutants in a large-scale urban mobility project.Results – The Inter 2 Project has significant potential to reduce pollutant emissions. In the most optimistic scenario, with a 40% speed increase, a reduction of at least 50% in total pollutant emissions is predicted, with 50.43% for CO emissions, 61.50% for VOCs, 44.50% for PM, and 56.74% for NOx. In the more conservative scenario, with a 30% speed increase, the reductions were 49.13% for CO emissions, 57.46% for VOCs, 4.08% for PM, and 19.16% for NOx.Theoretical/Methodological Contributions – Provision of crucial data for urban planning through a simplified approach, assisting in decision-making for sustainable mobility projects that balance traffic efficiency and environmental impact.Social and Environmental Contributions – The quantification of benefits related to optimizing bus lanes for public transport is essential for the success of sustainable urban mobility projects, which provide not only increased mobility efficiency but also significant reductions in atmospheric pollutants, resulting in improved air quality and reduced negative health impacts.
Keywords: Atmospheric Emission Reduction; Public Transport; Urban Mobility